Determinan Kualitas SDM dan Disparitas Distribusi Pendapatan di Kabupaten/Kota Provinsi Bali - I Made Cahyadi Arditya; Made Suyana Utama (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Dissimilarity in income distribution is one of the cases of development that often occurs as in regional development, where this dissimilarity in income distribution illustrates the comparison of income between communities. In Indonesia, in particular, the case of dissimilarity in the distribution of income is still a problem that often occurs to this day. The purpose of this study is to analyze the impact of capital expenditure and investment directly or indirectly on the quality of human resources and the dissimilarity of income distribution in the districts/cities of the Province of Bali. The analytical method used in this research is path analysis. The information used in this research is inferior information with 63 observations in the form of panel information or combination information between time series and cross sections. The results of this study are that capital expenditure and investment have a positive and important effect on the quality of human resources in the districts/cities of the Province of Bali, whereas capital expenditures, investment and quality of human resources have a negative and important effect on the disimilarity of income distribution in the districts/cities of the province of Bali. Capital spending and investment indirectly have a negative effect on the disimilarity of income distribution through the quality of human resources in the districts/cities of the Province of Bali.